Breast cancer treatment using Gold nanoparticles and gamma-ray photons With energy 12 Mev - Najim Abed Askouri (University of Thi-Qar Journal of Science, 2019)
Gold nanoparticles are characterised by their small size to volume ratio and extensive thermal stability. Gold nanoparticles (AuNPs) are an obvious choice in medical application due to their amenability of synthesis and functionalization, less toxicity and ease of detection. The present paper focuses on treatment of the breast cancer by high energy photons of gamma ray (12MeV.) and gold nanoparticles while preserving the shape of the breast and prevents the risk of recurrence of breast cancer. This of course in a minimum dose given for patient i.e. enhancing the radiotherapy that is used in breast cancer treatment due to pair production phenomena